Current account imbalances and structural adjustment in the euro area: how to rebalance competitiveness - Holger Zemanek; Ansgar Belke; Gunther Schnabl (Deutsches Institut für Wirtschaftsforschung (DIW), 2009)
Low international competitiveness of a set of euro area countries, which have become evident by large current account deficits and rising risk premiums on government bonds, is one of the most challenging economic policy issues for Europe. We analyse the role of private restructuring and public structural reforms for the urgently needed readjustment of intra-euro area imbalances. A panel regression reveals a significant impact of private restructuring and public structural reforms on intra-euro area competitiveness. This implies that private restructuring and public reforms are rather than public transfers the best way to preserve long-term economic stability in Europe.
Keywords: E24; F15; F16; F32; F33; 330; Structural reforms; competitiveness; current account imbalances; euro area; European Monetary Union; dynamic panel estimation; interaction term; Zahlungsbilanzungleichgewicht; Europäische Wirtschafts- und Währungsunion; Internationaler Wettbewerb; Wirtschaftsreform; Sozialreform; Wirtschaftliche Anpassung; EU-Staaten